Foliar Application of Boron and Irrigation Levels on the Performance of Lentil (Bangladesh Agronomy Journal, 2021)
The experiment was conducted to study the response of lentil to irrigation levels and different methods of boron application in relation to yield and yield contributing characters. Three levels of irrigation viz., I0: control (No irrigation), I1: one irrigation at 25 days after sowing (DAS), I2: two irrigations at 25 DAS and 40 DAS, and four levels of Boron viz., B0: control (No boron), B1: 80% recommended dose (RD) as basal + rest 20% as a foliar spray (FS) at pre-flowering (PF), B2: 60% RD as basal + rest 40% as FS at PF, B3: 40% RD as basal + rest 60% as FS at PF as treatment variables. It was found that the highest number of pods plant-1, number of seeds pod-1, 1000-seed weight, pod length, seed yield and stover yield was obtained with two irrigations. In contrast, B3 had a significant effect on the yield contributing characters of lentil. Results also revealed that numerically more seed yield (638.23 kg ha-1) was recorded in I2B3. Similar trend was found in case of stover yield (751.26 kg ha-1) and biological yield (1389.4 kg ha-1) from I2B3 combinations. These results suggested that combined application of irrigation at 25 and 40 DAS and boron at 40% RD as basal + rest 60% as FS at PF significantly enhanced the crop yields of lentil.Bangladesh Agron. J. 2021, 24(1): 129-138